Mechanistic insight into sorptive elimination of ibuprofen employing bi-directional activated biochar from sugarcane bagasse: Performance evaluation and cost estimation. Issue 4 (August 2018) - Chakraborty, Prasenjit; Show, Sumona; Banerjee, Soumya; Halder, Gopinath
Highlights: Physically and chemically activated biochar towards removal of ibuprofen. Surface modification by chemical activation exhibited better results. Kinetic studies on ibuprofen sorption suggested both chemisorption. Desorption study favoured the efficacy of the adsorbents. A maximum of 255.59 and 272.5 INR were incurred in adsorbent preparation. Abstract: The present investigation attempts in separating Ibuprofen (IBP) a pharmaceutical compound from aqueous solution tooled with two different activated form of sugarcane biochar as adsorbent. Differences in adsorption capability of the sugancane biochar were derived after activating its surface both physically and chemically. Operational conditions viz., initial ibuprofen concentration (1–50 mg/L), contact time (0.5–24 h), temperature (15–40 °C), adsorbent dose (0.033–5 g/L), pH (1–7) and agitation speed (100–200 rpm) were considered for both steam activated biochar (SPAB) and chemically activated biochar (SCAB) for sorptive elimination of IBP. Characterization of the adsorbents were carried out by scanning electron microscopy (SEM), Energy dispersive X-ray spectroscopy (EDX), FT-IR spectroscopy and determination of zero point charge (pH PZC ). IBP adsorption isotherm study was found to follow both Langmuir and Freundlich isotherm. Uptake capacity of SCAB and SPAB were 13.51 mg/g and 11.90 mg/g respectively. The sorption process obeyed pseudo second order kinetic model in both the cases. Exothermic, spontaneous and feasible nature of IBP adhesion on to SCAB and SPAB were confirmed from thermodynamic analysis. Estimated costs incurred in production of the adsorbents were found to be cheaper and reusability study was also validated for their usage of multiple cycles. SPAB and SCAB were able to remove 82% and 91% of ibuprofen from aqueous solution for a contact time of 18 and 12 hs respectively. Therefore, sugarcane bagasse derived biochar exhibited potential role towards adsorptive removal of ibuprofen from aqueous solution.